Effects of vanadium impurity on TiO2 properties - Stashans, A. (2015)
Our present work is based on the density functional theory (DFT) studies of TiO2 crystals doped with V impurities. Both rutile and anatase structures have been considered within the present research and different defect concentrations have been used as well. Our calculations reveal equilibrium geometry of the system showing atomic rearrangement around the point defect being mainly inward with respect to the impurity. Magnetism and electronic structure based on the density of states (DOS) patterns for both rutile and anatase crystals have been obtained and discussed in detail. It is shown that local magnetic moments arise mainly from the 3d states of the impurity atom with some admixture of 2p states from the vanadium-nearest O atoms. © 2015 World Scientific Publishing Company.